Validation of Pediatric Functional Assessment of Cancer Therapy Questionnaire (Version 2.0) in Brain Tumor Survivor Aged 13 Years and Older (Parent Form)(PedsFACT-BrS Parent of Adolescent) - Yoo, Hee-Jung (The Korean Neurosurgical Society, 2011)
OBJECTIVE: The aim of this study was to evaluate the reliability and validity of the Pediatric Functional Assessment of Cancer Therapy Questionnaire Brain Tumor Survivor (version 2.0) Aged 13 years and older (Parent Form) (pedsFACT-BrS parent of adolescent). METHODS: The pedsFACT-BrS parent of adolescent was translated and cross-culturally adapted into Korean, following standard Functional Assessment of Chronic Illness Therapy (FACIT) methodology. The psychometric properties of the pedsFACT-BrS parent of adolescent were evaluated in 170 brain tumor patient's mothers (mean age=43.38 years). Pretesting was performed in 30 mothers, and the results indicated good symptom coverage and overall comprehensibility. The participants also completed the Child Health Questionnaire Parent Form 50 (CHQ-PF-50), Neuroticism in Eysenck Personality Questionnaire, and Karnofsky score. RESULTS: In validating the pedsFACT-BrS parent of adolescent, we found high internal consistency, with Cronbach's α coefficients ranging from 0.76 to 0.94. The assessment of test-retest reliability using intraclass correlation coefficient revealed satisfactory values with ICCs ranging from 0.84 to 0.93. The pedsFACT-BrS for parent of adolescent also demonstrated good convergent and divergent validities when correlated with the Child Health Questionnaire Parent Form 50 (CHQ-PF-50) and the Neuroticism in Eysenck Personality Questionnaire. The pedsFACT-BrS parent of adolescent showed good clinical validity, and effectively differentiated between clinically distinct patient groups according to the type of treatment, tumor location, shunt, and Karnofsky score of parent proxy report. CONCLUSION: We confirmed that this reliable and valid instrument can be used to properly evaluate the quality of life of Korean adolescent brain tumor patients by their parents' proxy report.